Casteism: A Threat to Indian Society Ever: Exploring the impact of casteism on Indian society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The structure of Indian society is made according to unity in diversity and diversity in unity. The structure of Indian society is the sum total of diversities which includes many social classes, castes, religions, cultures and languages. Indian society is like vast ocean which merges much diversity in it. Indian society has number of different castes which is originally based on verna system, Brahmin, Kshatriyas, Vaishyas and Shudra. This system has broken the back bone of Indian democracy and also people of this country suffered a lot till ancient times due to this problem. The researcher shows the growth and effect of caste in India till ancient time in this paper.